Factors Caused Low Motivation to Learn Children Brokenhome at SMAN 2 Batang Anai - Sari, Yulia Ratna (Holistic Science, 2022)
This research is motivated by the existence of students who cause a lack of motivation to learn in children from broken home families, children learn to socialize to enter the community later. Children who have a complete and harmonious family will certainly have the personality and full attention of their parents, so that the child will have high self-confidence and a sense of responsibility. In fact, not all children can feel a complete and harmonious family. This research was conducted with a descriptive qualitative approach. The key informants in this study were 2 students and additional informants were 2 class teachers and 2 parents of students. The instrument used in this study is an interview guide. The data analysis techniques used are 1. Data reduction, 2. Data presentation, and 3. Conclusion drawing. The results of the study of student learning motivation are very influential with the way parents educate their children, there are parents who do not care about how their children study at home. And the lack of love from parents and support for children's learning. From the results of interviews conducted by BK teachers, there are several problems with broken home children where the child has a twin and they are not wanted by their parents so that they are separated from adoption by their siblings